Pengenalan Karakteristik Mineral dan Batuan Bagi Siswa Jurusan Geologi Pertambangan SMK Penerbangan Techno-Terapan Makassar - Amalia, Rizki; ., Sufriadin; ., Purwanto; Sutardjo Tui, Rini Novrianti; Hatta, Asta Arjunoarwan; Nur, Irzal; Ramli, Muhammad; Anas, Aryanti Virtanti; Widodo, Sri; Alvionita, A. Febbi; Gunawan, Syahrul; Aditya, Dzulkifli (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
Minerals and rocks are knowledge that everyone who wants to work in the mining industry must know. This community service activity aims to improve the understanding and skills of students majoring in Mining Geology at SMK Techno-Terapan Makassar in describing the characteristics of minerals and rocks. The problems faced by partners are the lack of laboratory facilities and the dominance of theoretical learning so practicums are not optimal. This training involved 39 students who were guided by lecturers and students from the Department of Mining Engineering, at Hasanuddin University. The training method includes material presentation, rock description tutorials, and mineral identification using 18 igneous, sedimentary, and metamorphic rock samples. Assessment is carried out through pre-test and posttest to measure participants' understanding. The results show an increase in the average score from 6.31 to 7.56, with a maximum score of 10, although not significant for some participants. Apart from providing increased understanding, this activity hands over rock samples to partners for further learning. In conclusion, this training is effective in improving students' practical skills related to minerals and rocks, which is an important provision for their future in the mining-geology field.